Motivated Misreporting in Smartphone Surveys. (February 2022) - Daikeler, Jessica; Bach, Ruben L.; Silber, Henning; Eckman, Stephanie
Filter questions are used to administer follow-up questions to eligible respondents while allowing respondents who are not eligible to skip those questions. Filter questions can be asked in either the interleafed or the grouped formats. In the interleafed format, the follow-ups are asked immediately after the filter question; in the grouped format, follow-ups are asked after the filter question block. Underreporting can occur in the interleafed format due to respondents' desire to reduce the burden of the survey. This phenomenon is called motivated misreporting. Because smartphone surveys are more burdensome than web surveys completed on a computer or laptop, due to the smaller screen size, longer page loading times, and more distraction, we expect that motivated misreporting is more pronounced on smartphones. Furthermore, we expect that misreporting occurs not only in the filter questions themselves but also extends to data quality in the follow-up questions. We randomly assigned 3, 517 respondents of a German online access panel to either the PC or the smartphone. Our results show that while both PC and smartphone respondents trigger fewer filter questions in the interleafed format than the grouped format, we did not find differences between PC and smartphone respondents regarding the number of triggered filter questions. However, smartphone respondents provide lower data quality in the follow-up questions, especially in the grouped format. We conclude with recommendations for web survey designers who intend to incorporate smartphone respondents in their surveys.